AN ESTIMATOR OF MOMENT OF INERTIA OF MAGIC SQUARE ARRAY OF MASSES (FUDMA JOURNAL OF SCIENCES, 2022)
The classical definition of magic square of order  is a square array of consecutive natural numbers from 1 to  such that the raw, column and diagonal sum add up to the same number. When the magic square entries are considered as an array of masses of a rigid body, it is established that its moment of inertia is a function of  This work consider a more general magic array of masses of a rigid body to establish its inertial moment as a function of the magic sum and the central entry of the array. The paper further discusses the advantage of this development.
Keywords: Magic square, moment of inertia, kinetic energy, axis